2017
DOI: 10.1177/0954406217736552
|View full text |Cite
|
Sign up to set email alerts
|

Iron-based reversible adhesives: Effect of particles size on mechanical properties

Abstract: A hot melt adhesive -mainly used for bonding plastic component in automotive field -was modified with different ironbased particles to give it a reversible behaviour. Mechanical and physical properties of these reversible adhesives were experimentally assessed in the work. The modified adhesives, coupled with electromagnetic induction, are able to guarantee separation of the joints without any damage to the substrates for recycling, reuse or repairing of components. Single lap joint specimens were prepared usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
4
16
0
Order By: Relevance
“…In order to obtain the best resolution, secondary electron emission signals were used with an accelerating voltage of 1.4 kV. The specimens were properly coated with gold to have better images [29]. The results of the Scanning Electron Microscope (SEM) are discussed in Section 3.3.…”
Section: Specimens Preparationmentioning
confidence: 99%
“…In order to obtain the best resolution, secondary electron emission signals were used with an accelerating voltage of 1.4 kV. The specimens were properly coated with gold to have better images [29]. The results of the Scanning Electron Microscope (SEM) are discussed in Section 3.3.…”
Section: Specimens Preparationmentioning
confidence: 99%
“…The heating happens very fast and melts or decomposes the adhesive material near the primer layer or the primer layer itself. This process causes a loss in strength so that the bonded joint can be easily debonded [ 179 , 193 , 194 , 195 ].…”
Section: Disassembling Strategies For Maintenance and End-of-life mentioning
confidence: 99%
“…Lu et al [ 5 ] and Banea et al [ 6 ] reported the newest patented and proposed in literature technologies able to ease the separation processes of adhesive joints. These new and innovative technologies have been studied because the current traditional techniques (the use of chemical agents, heat, or mechanical cut) lead to damage to substrates or components [ 5 , 6 , 7 ]. Among the techniques presented in [ 5 , 6 ], some of them can be fully reversible since they use thermoplastic adhesives that can be remelted (as compared to thermoset adhesives) and thus they can be used for repair, overhaul or avoid waste during the bonding operations.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, the need to find alternative techniques is crucial to promote the rapid separation of adhesively bonded components. Many studies [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ] have been presented in the literature regarding the dismantling of the adhesive joints of thermoplastic components. The use of iron oxide nanoparticles dispersed in a holt-melt adhesive that is activable through induction heating has been extensively studied by Ciardiello et al [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation